Is the budget for results a strategy to right public spending in Colombia? (2015)
This essay is a reflection about the main proposals of experts on the budget for results like strategy to execute the public spending. Due to the importance to evaluate and strengthen the Colombian budget system given the impact in the macroeconomic stability of country and especially in the efficient carry out of public resources. There is no doubt that the budget for results is a significant instrument of fiscal policy and economic of the countries. On that subject the new public management stressesthe necessity of a management strategy for results in base of the budget for results like one of the pillars of management and such as an importance element in the process of generation of public valor, because it contribute to the resources assignment of an efficient and objective way in benefit of population of the country and according to the proposals of experts in this topic that was checked, is an excellent strategy for improving the currently perspective of the Colombian budget system.